Improving the resilience and workforce of health systems for women's, children's, and adolescents' health. (14th September 2015) - Campbell, James; Cometto, Giorgio; Rasanathan, Kumanan; Kelley, Edward; Syed, Shamsuzzoha; Zurn, Pascal; Bernis, Luc de; Matthews, Zoe; Benton, David; Frank, Odile; Nove, Andrea
Abstract : To achieve the sustainable development goals related to maternal, child, and adolescent health, countries need to integrate targeted interventions within their national health strategies and leverage them into financing, workforce, and monitoring capacity across the system, say James Campbell and colleagues .